Crystal structure of family 4 uracil–DNA glycosylase fromSulfolobus tokodaii and a function of tyrosine 170 in DNA binding. Issue 19 (28th August 2015) - Kawai, Akito; Higuchi, Shigesada; Tsunoda, Masaru; Nakamura, Kazuo T.; Yamagata, Yuriko; Miyamoto, Shuichi
Abstract : Uracil–DNA glycosylases (UDGs) excise uracil from DNA by catalyzing the N ‐glycosidic bond hydrolysis. Here we report the first crystal structures of an archaeal UDG ( sto UDG). Compared with other UDGs, sto UDG has a different structure of the leucine‐intercalation loop, which is important for DNA binding. The sto UDG–DNA complex model indicated that Leu169, Tyr170, and Asn171 in the loop are involved in DNA intercalation. Mutational analysis showed that Tyr170 is critical for substrate DNA recognition. These results indicate that Tyr170 occupies the intercalation site formed after the structural change of the leucine‐intercalation loop required for the catalysis. Abstract : Crystal structures of sto UDG in the free form and in the complex form with uracil were determined at 1.7 Å resolution. The leucine‐intercalation loop structure of sto UDG differs from the other family 4 UDGs. Tyr170 is the intercalating residue of sto UDG. sto UDG will require a structural change to recognize the substrate DNA.